Ny typ av fotskålar från Danmark - Kaelas, Lili (Kuml, 1958)
A New Type of Pedestal Bowls from Denmark. While going through the collection of Stone-Age specimens in the Haderslev Amt's Museum during the summer of 1956 the author came across two fragments of pedestal bowls which differ completely from the pedestal bowls characteristic of the South Scandinavian funnel-beaker culture. The one fragment came originally from the remarkable Stone-Age cemetery at Harreby in Hygum parish in South Jutland, and comprises the junction between the bowl and the pedestal (fig. 1). Unfortunately more exact details of the circumstances of discovery are lacking. It is only 3 cms. in diameter, has a sharp curvature, and is decorated with the typical ornamentation of the local funnel-beaker culture, rows of close-set horizontal bows. The other fragment of a pedestal bowl comes from the area outside the passage opening of a passage grave at Avnevig in Fjelstrup parish in Haderslev Amt. This fragment, too, comprises the junction between bowl and pedestal of a comparatively small pedestal bowl of the same type as the Harreby bowl, i. e. possessing a curved pedestal (fig. 2). This pedestal-junction, too, is quite small (about 5.5 cms. in diameter). In contrast to the Harreby bowl the ornamentation of the Avnevig bowl diverges from the normal ornamentation of the South Scandinavian pedestal bowls: the surviving portion of the junction is ornamented with close-set, relatively thick, horizontal rows of impressions, arranged in two groups. Both the shape and the foreign nature of the decoration make it tempting to regard this specimen as an import from a non-Scandinavian area. The pedestal bowl is, however, much too fragmentarily preserved for it to be possible at the moment to express an opinion concerning its possible place of origin. The rows of bows on the Harreby pedestal bowl, an ornamentation which in South Denmark is distinctive of the period of the Klintebakken settlement, date the bowl to Middle Neolithic Period Ib 3). In the case of the Avnevig pedestal bowl the place of discovery, the passage grave, provides a terminus ante quem. It is in this connection not without interest to mention that the chamber of the Avnevig passage grave is of roundish polygonal plan, narrowing somewhat towards the passage, and measuring 2 x 2.1 meters (figs. 6-7). Passage graves of this shape (characterized by Daniel as passage graves of Pavia type after the cemetery of that name in Portugal 9) have since the days of Montelius rightly been regarded as typologically the earliest forms in South Scandinavia. In agreement with the earliest objects found here (including a Troldebjerg bowl with symmetrically arranged decoration, fig. 8, and a fragment of a ladle with concentric rows of bows, fig. 3) the Avnevig passage grave has been attributed to the date of the Klintebakken settlement (Period Ib 10). The pedestal bowls hitherto known in the Danish material belong exclusively to the first two periods of the Middle Neolithic. It has long been recognised that pedestal bowls and ladies within the orbit of the South Scandinavian funnel-beaker culture are emanations from the large band-ware culture complex. Discussion of the origin of these forms has in the main been aimed at proving some particular band-ware culture group as the connecting link. Formerly it was usual to point to the Jordansmühl culture as this link, but later research has been able, for good stylistic reasons, to reject the pedestal bowls of this culture as possible prototypes of the pedestal bowls of the Scandinavian funnelbeaker culture 13). The Scandinavian pedestal bowls possess a comparatively sharply angled junction between bowl and pedestal, and a broad, conical, normally tall pedestal (generally higher than, or at least as high as, the bowl). The Jordansmühl culture, on the other hand, is the only band-ware culture group which possesses pedestal bowls with, in general, a more rounded section and frequently an inward curving junction between bowl and pedestal 17). So far as shape is concerned there is a striking resemblance between the two South Danish pedestal bowls described above and the Jordansmühl pedestal bowls. That direct contact has taken place between the Jordansmühl and the funnel-beaker cultures within the area of the latter culture is shown, inter alia, by the well known pedestal bowl, probably imported from the area of the Jordansmühl culture, found in the passage grave at Drouwen in Drente province in Holland 18). The discovery of pedestal bowls of Jordansmühl type within the sphere of the South Scandinavian funnel-beaker culture in the Middle Neolithic is of great importance for the comparative chronology of both cultures. The dating of the Jordansmühl culture has shown considerable instability. Most recently it has been treated in detail by Becker who, on grounds of the discovery of objects from the eastern funnel-beaker culture, in particular of the collared flasks in the well known graves nos. 20 and 28 at Jordansmühl itself, considers it to correspond exclusively with his Early Neolithic C 23). Recently, however, the validity of the objects from these two graves as evidence for regarding the Jordansmühl culture as parallel to the early phase of the funnel-beaker culture has been brought into question 24). Schwabedissen, who has also recently discussed the question of the dating of the Jordansmühl culture, rather considers it to correspond to Period Ib of the Scandinavian Middle Neolithic 25). This latter dating (at least as suggesting that the Jordansmühl culture was still flourishing at this period) seems to a certain degree supported by the type of pedestal bowl here described, one hitherto unknown in Denmark. It also indicates that, on the evidence of discoveries hitherto made, the contact - direct or indirect - between the Jordansmühl culture and the South Scandinavian funnel-beaker culture probably was somewhat later than the contact with the band-ware culture complex which introduced the prevalent types of pedestal bowls and ladies, since these occur in the Scandinavian area at Troldebjerg as early as Period la. Lili Kaelas.